Understanding Developing Country Strategic Responses to the Enhancement of Food Safety Standards - Henson, Spencer; Jaffee, Steven (2012)
This paper explores the competing concepts of 'standards as barriers' and 'standards as catalysts' in the context of food safety standards in international trade in agricultural and food products. Through a review of existing evidence of the impact of food safety standards on developing country exports of agricultural and food products and the results of a series of country- and product-specific case studies, it is suggested that food safety standards can act as both a barrier to trade and the basis of competitive positioning for developing countries in international markets. This suggests that broad conclusions about the trade effects of food safety standards on developing countries are problematic, rather the level and ways in which agricultural and food exports are impacted can be product, country, standard and even firm-specific.